Weaving about the series entrance exam: challenges and possibilities (Research, Society and Development, 2021)
Brazil has significant differences regarding educational inequalities. Only 18.1% of young people attend higher education and the majority of students who enter an undergraduate course belong to families with income above 5 minimum wages. Even with quota policies, we realize that inequalities in access and permanence in higher education have not been overcome. The method of access to higher education is recognized as one of the instruments that favor inequality, as poor and rich students are evaluated based on the same criteria, but have different and unequal opportunities to access knowledge. The general objective of this study was to discuss the effects of the serial entrance exam in the democratization of admission to higher education. Therefore, a literature review was carried out. The results indicate that serial entrance exam methods exist in some higher education institutions in Brazil since the 1980s and contribute to the increase in socio-educational inequalities. Experiences of automatic entry into higher education, as in the case of Argentina, contribute to the increase in the number of students from lower classes entering undergraduate courses, although they do not guarantee permanence. It is concluded that the proposed serial entrance exam is effective in a project to increase inequalities and exclusion of the poorest students from higher education.